The Credit Risk of China’s Listed Commercial Banks and Its Determinants - Huang, Yu-Han (2022)
Among the many risks that commercial banks face, credit risk is one of the primary risks that can lead to bank failures and trigger regional or even global economic crises. The core of credit risk management is to measure credit risk, identify its determinants, and take targeted measures to effectively reduce credit risk. As a result, this study employs the KMV model to calculate the distance to default of the three most important types of commercial banks in China to obtain a reliable indicator of credit risk. Furthermore, a multiple linear regression model with panel data is used to empirically analyse the macro and micro factors that influence the credit risk of Chinese commercial banks in order to determine the extent to which these factors influence credit risk.